Clinical and molecular features of patients with amyotrophic lateral sclerosis and SOD1 mutations: a monocentric study - Gagliardi, Delia; Ripellino, Paolo; Meneri, Megi; Del Bo, Roberto; Antognozzi, Sara; Comi, Giacomo Pietro; Gobbi, Claudio; Ratti, Antonia; Ticozzi, Nicola; Silani, Vincenzo; Ronchi, Dario; Corti, Stefania (Frontiers in Neurology, 2023)
Introduction: SOD1 was the first gene associated with both familial and sporadic forms of Amyotrophic Lateral Sclerosis (ALS) and is the second most mutated gene in Caucasian ALS patients. Given their high clinical and molecular heterogeneity, a detailed characterization of SOD1-ALS patients could improve knowledge about the natural history of this disease. Here, we aim to provide a clinical and molecular description of a monocentric cohort of SOD1-ALS patients. Methods: ALS patients referring to the Neurology Unit of our center between 2008 and 2021 were clinically assessed and underwent molecular testing for SOD1. Segregation studies in available family members and in silico analysis were performed to sustain the pathogenicity of the identified SOD1 variants. Results: Among the 576 patients in our cohort, we identified 19 individuals harboring a mutation in SOD1 (3.3%), including 15 (78.9%) with a familial and 4 (21.1%) with a sporadic form. Spinal onset of the disease was observed in all patients and survival was extremely variable, ranging from 8 months to over 30 years. Twelve different SOD1 missense variants were identified in our cohort, including one novel mutation (p.Pro67Leu). Discussion: In the present series we provided the first description of an Italian monocentric cohort of SOD1-ALS patients, and we expanded the repertoire of SOD1 mutations. Our cohort present several remarkable features, including variable expressivity in the same family, atypical presentation (ataxia, cognitive impairment and other extra-motor symptoms) and different mode of inheritance of a given mutation in the same family. Given the recent authorization of SOD1-directed antisense oligonucleotide for the use in SOD1-ALS patients, we recommend the prompt screening for SOD1 mutations in novel ALS patients with familiar or sporadic presentations.